VEGETATION STRUCTURE AND REGENERATION OF VAN PANCHAYAT FORESTS IN KUMAUN HIMALAYA, UTTARAKHAND - Pandey, Jyoti; Lodhiyal, L. S. (International Journal of Environment, 2015)
Study deals with the vegetation structure and regeneration in Van Panchayat forests in Nainital of Kumaun Himalaya. The analysis of forest was done in three sites i.e. hill top, hill slope and hill base forest site. Tree density in Jungalia and Soangaon Van Panchayats ranged from 80-2070 and 50-5270 individual ha-1 respectively. Importance value index was 8.11-137.29 in Jungalia gaon Van Panchayat while 15.65-143.04 in Soangaon Van Panchayat. Species diversity ranged from 0.09-1.97 in Jungalia gaon and 0.17-0.44 in Soangaon Van Panchayat. The occurrence of higher number of seedlings in both the Van Panchayat showed good regeneration potential of tree species. International Journal of Environment Volume-4, Issue-3, June-August 2015 Page: 69-80